Anode Materials and Batteries

JP7637919B2Active Publication Date: 2025-03-03PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022518615
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-28
Filing Date
2021-02-12
Publication Date
2025-03-03
Estimated Expiration
2041-02-12

AI Technical Summary

Benefits of technology

【0006】 本開示によれば、固体電池の充電レート特性を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637919000002
    Figure 0007637919000002
  • Figure 0007637919000003
    Figure 0007637919000003
  • Figure 0007637919000001
    Figure 0007637919000001
Patent Text Reader

Abstract

A negative electrode material 1000 of the present disclosure includes a negative electrode active material 310, a solid electrolyte 300, and a coating material that coats the negative electrode active material 310. The coating material is represented by compositional formula (1), wherein a, b, and c are positive real numbers, A is at least one element selected from the group consisting of P and S, and X is F or O. (1): LiaAbXc
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to negative electrode materials and batteries. [Background technology]

[0002] Patent Document 1 discloses a powdered negative electrode active material made of amorphous coated graphite in which at least a portion of the surface of a graphitic particle is coated with amorphous carbon. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 4729716 Summary of the Invention [Problem to be solved by the invention]

[0004] Batteries using solid electrolytes have inferior charge rate characteristics compared to batteries using electrolyte solutions, and therefore there is a demand for improving the charge rate characteristics of solid electrolyte batteries. [Means for solving the problem]

[0005] The present disclosure relates to A negative electrode active material; A solid electrolyte; A coating material that coats the negative electrode active material; Including, The coating material is represented by the following composition formula (1): Li a A b X c (1) where a, b, and c are positive real numbers. A is at least one selected from the group consisting of P and S; X is F and O; A negative electrode material is provided. Effect of the Invention

[0006] According to the present disclosure, it is possible to improve the charge rate characteristics of a solid-state battery. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic configuration of a negative electrode material 3000 in the first embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a schematic configuration of a battery 2000 in the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] (Findings on which this disclosure is based) In recent years, development of solid-state batteries using solid electrolytes has been progressing. Compared with lithium-ion batteries using electrolytes, the interface area between the negative electrode active material and the electrolyte tends to be smaller in solid-state batteries. When the interface area decreases, the charge rate characteristic, which is the input rate characteristic when lithium ions are inserted into the negative electrode active material, decreases. Therefore, the charge rate characteristic of solid-state batteries tends to be inferior to that of lithium-ion batteries using electrolytes. In order to popularize solid-state batteries, there is a demand for improvement in the charge rate characteristic, which leads to a reduction in charging time.

[0009] In the field of lithium ion liquid batteries using electrolytes, various compounds that dissolve in organic electrolytes have been studied. A coating is formed on the surface of the negative electrode by utilizing the reduction reaction of the compound on the surface of the negative electrode. In this way, attempts have been made to improve the properties of the negative electrode active material. However, in solid-state batteries, the electrolyte is solid, so conventional methods cannot be simply applied. In other words, in the field of solid-state batteries, there have been almost no attempts to improve the properties by coating the negative electrode active material with a coating material.

[0010] One method for improving the charge rate characteristic is as follows. That is, the mass of the negative electrode active material is reduced to reduce the capacity per unit area. This reduces the amount of current per unit area, and the charge rate characteristic by the hourly rate current can be improved. However, when the mass of the negative electrode active material is reduced, the mass of the positive electrode active material must also be reduced. As a result, the capacity of the battery is reduced. Since the volume of the members that do not contribute to the capacity, such as the current collector and the insulating layer, does not change, the proportion of the material that contributes to the capacity is relatively reduced. Therefore, the energy density of the battery per unit volume or per unit mass is also reduced.

[0011] The present disclosure has been made in consideration of the above circumstances, and provides a negative electrode material that can improve the charge rate characteristics of a battery.

[0012] (Summary of one aspect of the present disclosure) The negative electrode material according to the first aspect of the present disclosure is A negative electrode active material; A solid electrolyte; A coating material that coats the negative electrode active material; Including, The coating material is represented by the following composition formula (1): Li a A b X c (1) where a, b, and c are positive real numbers. A is at least one selected from the group consisting of P and S; X is F and O.

[0013] By coating the negative electrode active material with the coating material represented by formula (1), the charge rate characteristics of the battery can be improved.

[0014] In a second aspect of the present disclosure, for example, in the negative electrode material according to the first aspect, the coating material is SO x F yAccording to such a configuration, a better coating layer is formed, so that deterioration of the solid electrolyte can be suppressed and the charge rate characteristics of the battery can be improved more effectively.

[0015] In the third aspect of the present disclosure, for example, in the negative electrode material according to the second aspect, the coating material may contain Li, S, O, and F. With this configuration, a better interface between the active material and the solid electrolyte can be formed, and the charge rate characteristics of the battery can be improved more effectively.

[0016] In a fourth aspect of the present disclosure, for example, in the negative electrode material according to the first aspect, the coating material is PO x F y According to such a configuration, a better interface between the active material and the solid electrolyte can be formed, and therefore the charge rate characteristics of the battery can be improved more effectively.

[0017] In a fifth aspect of the present disclosure, for example, in the negative electrode material according to the fourth aspect, the coating material may contain Li, P, O, and F. With this configuration, a better interface between the active material and the solid electrolyte can be formed, and the charge rate characteristics of the battery can be improved more effectively.

[0018] In a sixth aspect of the present disclosure, for example, in the negative electrode material according to the first aspect, the coating material is LiSO 3 F and LiPO 2 F 2 By using these materials as the coating material, the charge rate characteristics of the battery can be improved.

[0019] In the seventh aspect of the present disclosure, for example, in the negative electrode material according to any one of the first to sixth aspects, the thickness of the coating material layer may be 0.5 nm or more and 20 nm or less. When the thickness of the coating material layer is adjusted to such a range, the Li-ion conductivity of the coating material layer can be sufficiently ensured, and the charge rate characteristics of the battery can be further improved.

[0020] In an eighth aspect of the present disclosure, for example, in the negative electrode material according to any one of the first to seventh aspects, the solid electrolyte may include at least one selected from the group consisting of a sulfide solid electrolyte, a halide solid electrolyte, and an oxyhalide solid electrolyte. With this configuration, the ionic conductivity of the solid electrolyte can be improved.

[0021] In a ninth aspect of the present disclosure, for example, in the negative electrode material according to any one of the first to eighth aspects, the negative electrode active material may contain at least one selected from the group consisting of carbon materials and alloy-based active materials that form an alloy with lithium. Use of the alloy-based active material can improve the energy density of the battery.

[0022] In a tenth aspect of the present disclosure, for example, in the negative electrode material according to any one of the first to ninth aspects, the negative electrode active material may contain graphite. Graphite is suitable as a negative electrode active material because it has a small expansion coefficient during a lithium ion insertion reaction.

[0023] In an eleventh aspect of the present disclosure, for example, in the negative electrode material according to any one of the first to tenth aspects, the solid electrolyte may have lithium ion conductivity. With this configuration, the negative electrode material can be used in a lithium ion battery.

[0024] A battery according to a twelfth aspect of the present disclosure comprises: A negative electrode comprising the negative electrode material according to any one of the first to eleventh embodiments; A positive electrode and an electrolyte layer provided between the positive electrode and the negative electrode; Equipped with.

[0025] According to the battery of the present disclosure, the above-mentioned advantages are obtained in the negative electrode.

[0026] A method for producing a negative electrode material according to a thirteenth aspect of the present disclosure includes the steps of: A method for producing a negative electrode material including a negative electrode active material and a coating material that coats the negative electrode active material, preparing a solution containing the coating material and a first solvent; mixing the solution with the negative electrode active material to prepare a mixture; and coating the negative electrode active material with the coating material by removing the first solvent from the mixture.

[0027] According to the method of the present disclosure, the negative electrode active material can be efficiently coated with the coating material, and since drying at a high temperature is not essential, the method is simple.

[0028] In a fourteenth aspect of the present disclosure, for example, in the method for producing an anode material according to the thirteenth aspect, a slurry-like anode material may be produced by kneading a solid electrolyte and the anode active material coated with the coating material using a second solvent in which the coating material is insoluble. With this configuration, the anode can be produced efficiently.

[0029] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0030] (Embodiment 1) FIG. 1 is a cross-sectional view showing a schematic configuration of a negative electrode material 3000 in the first embodiment.

[0031] The negative electrode material 3000 in the first embodiment includes a coated active material 330 and a solid electrolyte 300. The coated active material 330 and the solid electrolyte 300 are in contact with each other.

[0032] The coated active material 330 includes a negative electrode active material 310 and a coating layer 320. The coating layer 320 is provided on the surface of the negative electrode active material 310. The coating layer 320 is a layer including a coating material. The negative electrode active material 310 is coated with the coating material. In the coating layer 320, the coating material is in a solid state.

[0033] The coating material is represented by the following composition formula (1), where a, b, and c are positive real numbers. A is at least one selected from the group consisting of P and S. X is F or O.

[0034] Li a A b X c (1)

[0035] The coating material represented by formula (1) is contained in the coating layer 320, thereby improving the charge rate characteristics of the battery. Although the principle behind this is not necessarily clear, it is believed that various factors such as the voltage resistance of the coating material, the oxidation resistance of the solid electrolyte 300, the reactivity of the coating material with the negative electrode active material 310, the reactivity of the coating material with the solid electrolyte 300, and the physical contact between the negative electrode active material 310 and the solid electrolyte 300 are involved in combination. It is believed that the coating material plays a role in promoting the exchange of lithium ions between the negative electrode active material 310 and the solid electrolyte 300 on the surface of the negative electrode active material 310. The coating layer 320 may contain only the coating material, excluding inevitable impurities.

[0036] According to the above-mentioned configuration, a better interface between the coated active material 330 and the solid electrolyte 300 can be formed, so that the charge rate characteristics of the battery can be improved more effectively.

[0037] The coating material is SO x F y x and y are values ​​that satisfy x>0 and y>0. Even if the stoichiometric composition is x+y=3 or 4, actual chemical analysis reveals that x and y are non-stoichiometric.

[0038] According to the above-mentioned configuration, a better coating layer 320 is formed, so that deterioration of the solid electrolyte 300 can be suppressed, and the charge rate characteristics of the battery can be improved more effectively.

[0039] The coating material may include Li, S, O and F.

[0040] According to the above-mentioned configuration, a better interface can be formed between the coated active material 330 and the solid electrolyte 300, and therefore the charge rate characteristics of the battery can be improved more effectively. The coating material may be composed of Li, S, O, and F, excluding inevitable impurities.

[0041] The coating material is PO x F y x and y are values ​​that satisfy x>0 and y>0. Even if the stoichiometric composition is x+y=3 or 4, actual chemical analysis reveals that x and y are non-stoichiometric.

[0042] According to the above-mentioned configuration, a better interface between the coated active material 330 and the solid electrolyte 300 can be formed, so that the charge rate characteristics of the battery can be improved more effectively.

[0043] The coating material may include Li, P, O and F.

[0044] According to the above-mentioned configuration, a better interface can be formed between the coated active material 330 and the solid electrolyte 300, and therefore the charge rate characteristics of the battery can be improved more effectively. The coating material may be composed of Li, P, O, and F, excluding inevitable impurities.

[0045] The coating material may be a phosphoric acid-based material or a sulfonic acid-based material. 4 , LiPO 2 F 2 , Li 2 PO 3 F and LiSO 3 It may contain at least one selected from the group consisting of:

[0046] The coating material is preferably LiSO 3 F and LiPO 2 F 2 It may include at least one selected from the group consisting of:

[0047] By using these materials as the coating material, the charge rate characteristics and life characteristics of the battery can be further improved.

[0048] The coating layer 320 may exclude inevitable impurities and contain only the compound represented by formula (1). With this configuration, the effect of improving the charge rate characteristics of the battery can be reliably obtained.

[0049] The ratio of the mass of the coating material to the mass of the coated active material 330 may be greater than 0 mass% and less than or equal to 10.0 mass%. The ratio of the mass of the coating material to the mass of the coated active material 330 may be greater than 0 mass% and less than or equal to 5.0 mass%. The ratio of the mass of the coating material to the mass of the coated active material 330 may be greater than 0 mass% and less than or equal to 3.0 mass%.

[0050] When the coating amount is adjusted to fall within this range, lithium ions are smoothly exchanged between coated active material 330 and solid electrolyte 300, making it possible to more effectively improve the charge rate characteristics of the battery.

[0051] The ratio of the mass of the coating material to the mass of the coated active material 330 can be obtained, for example, by the following method. The coated active material 330 is dissolved in an acid or the like to prepare an aqueous solution. Then, the elements contained in the aqueous solution are quantified by inductively coupled plasma (ICP) emission spectrometry. This makes it possible to obtain the ratio of the mass of the coating material to the mass of the coated active material 330. At this time, attention may be paid to the quantitative value of the elements contained in only one of the negative electrode active material 310 and the coating material. After dissolving the coating material in pure water, the dissolved ions may be detected using an ion chromatograph to quantify the elements.

[0052] The coating material may have a peak in the range of 685±7 eV in the XPS spectrum measured using AlKα radiation. In the range of 685±7 eV, a peak derived from the F1s orbital is detected. In particular, a peak centered at 685 eV indicates the presence of Li-F bonds. The bond between Li and F is stronger than the bond between Li and other anions, and is therefore stable. Therefore, the coating material having a peak in the above range is less likely to deteriorate even during the charge / discharge reaction, and can continuously improve the charge rate characteristics.

[0053] The thickness of the coating layer 320 may be 0.5 nm or more and 20 nm or less. By making the thickness of the coating layer 320 0.5 nm or more, the charge rate characteristics of the battery can be further improved. By making the thickness of the coating layer 320 20 nm or less, the Li ion conductivity is improved. More preferably, the thickness of the coating layer 320 may be 0.5 nm or more and 10 nm or less.

[0054] There is no particular limitation on the method for measuring the thickness of the coating layer 320. For example, in XPS measurement, the thickness can be estimated by observing a specific peak due to the coating material while scraping the surface of the coated active material 330 by ion beam etching. Alternatively, the thickness of the coating layer 320 may be measured by direct observation using a transmission electron microscope.

[0055] The coating layer 320 may cover the entire surface of the particles of the negative electrode active material 310. This can prevent direct contact between the particles of the negative electrode active material 310 and the particles of the solid electrolyte 300, thereby suppressing side reactions in the solid electrolyte 300. This can improve the charge / discharge efficiency.

[0056] Alternatively, the coating layer 320 may cover only a portion of the surface of the particle of the negative electrode active material 310. The particles of the negative electrode active material 310 directly contact each other through the portion not having the coating layer 320, thereby improving the electronic conductivity between the particles of the negative electrode active material 310. This enables the battery to operate at a high output.

[0057] The shape of solid electrolyte 300 in the first embodiment is not particularly limited and may be, for example, needle-like, spherical, oval-spherical, etc. For example, solid electrolyte 300 may be in the form of particles.

[0058] For example, when the solid electrolyte 300 in the first embodiment is particulate (e.g., spherical), the median diameter may be 100 μm or less. When the median diameter of the solid electrolyte 300 is 100 μm or less, the coated active material 330 and the solid electrolyte 300 can form a good dispersion state in the negative electrode material 3000. This improves the charge rate characteristics of the battery. In the first embodiment, the median diameter of the solid electrolyte 300 may be 10 μm or less.

[0059] According to the above configuration, in the negative electrode material 3000, the coated active material 330 and the solid electrolyte 300 can be in a well-dispersed state.

[0060] In the first embodiment, the median diameter of the solid electrolyte 300 may be smaller than the median diameter of the coated active material 330 .

[0061] According to the above configuration, the solid electrolyte 300 and the coated active material 330 in the negative electrode material 3000 can be in a better dispersed state.

[0062] The median diameter of the coated active material 330 may be not less than 0.1 μm and not more than 100 μm.

[0063] When the median diameter of the coated active material 330 is 0.1 μm or more, the coated active material 330 and the solid electrolyte 300 can be well dispersed in the negative electrode material 3000. As a result, the charge / discharge characteristics of the battery are improved.

[0064] When the median diameter of the coated active material 330 is 100 μm or less, a sufficient diffusion rate of lithium is ensured within the coated active material 330. This enables the battery to operate at high power output.

[0065] The median diameter of the coated active material 330 may be larger than the median diameter of the solid electrolyte 300. This allows the coated active material 330 and the solid electrolyte 300 to form a good dispersed state.

[0066] In the negative electrode material 3000 in the first embodiment, the particles of the solid electrolyte 300 and the particles of the coated active material 330 may be in contact with each other as shown in Fig. 1. The solid electrolyte 100 may fill the spaces between the particles of the coated active material 330. In this case, the coating layer 320 and the solid electrolyte 300 are in contact with each other.

[0067] The negative electrode material 3000 in the first embodiment may include a plurality of solid electrolyte 300 particles and a plurality of coated active material 330 particles.

[0068] In the negative electrode material 3000, the content of the solid electrolyte 300 and the content of the coated active material 330 may be the same as or different from each other.

[0069] In this specification, the term "median diameter" refers to the particle diameter when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measuring device or an image analyzer.

[0070] The solid electrolyte 300 may have lithium ion conductivity, in which case the anode material 3000 may be used in a lithium ion battery.

[0071] The solid electrolyte 300 may include at least one selected from the group consisting of a sulfide solid electrolyte, a halide solid electrolyte, and an oxyhalide solid electrolyte.

[0072] The above configuration can improve the ionic conductivity of the solid electrolyte 300. This can reduce the resistance of the battery.

[0073] As a halide solid electrolyte, Li 3 YX' 6 , Li2 MgX' 4 , Li 2 FeX' 4 , Li(Al,Ga,In)X' 4 , Li 3 (Al,Ga,In)X' 6 etc.

[0074] As for the oxyhalide solid electrolyte, Li a (Ta,Nb) b O c X' d a, b, c, and d are each independently a value greater than 0. X′ includes at least one selected from the group consisting of F, Cl, Br, and I.

[0075] As for sulfide solid electrolytes, Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 S.B. 2 S 3 , Li 2 S-GeS 2 , Li 3.25 Ge 0.25 P 0.75 S 4 , Li 10 GeP 2 S 12 These include LiX', Li 2 O, M.O. q , Li p MO q In this case, the element X' in "LiX'" is at least one element selected from the group consisting of F, Cl, Br, and I. q " and "Li p MO q "The element M is at least one element selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe, and Zn. q " and "Li p MO q " In this equation, p and q are independent natural numbers.

[0076] In the present disclosure, when an element in a formula is expressed as "(Al, Ga, In)", this notation indicates at least one element selected from the group of elements in the parentheses. That is, "(Al, Ga, In)" is synonymous with "at least one element selected from the group consisting of Al, Ga, and In". The same applies to other elements.

[0077] Various solid electrolytes can be produced, for example, by the following methods.

[0078] Prepare raw material powders so that they form the desired composition. For example, Li 3 YBr 3 Cl 3 To prepare the 3 and are prepared in a molar ratio of 3: 1. The composition of the solid electrolyte can be adjusted by adjusting the type of raw material powder, the blending ratio of the raw material powder, and the synthesis process.

[0079] After thoroughly mixing the raw material powders, the raw material powders are mixed together, pulverized, and reacted using a mechanochemical milling method. Alternatively, after thoroughly mixing the raw material powders, the resulting mixture may be fired in an inert atmosphere. This produces the desired solid electrolyte.

[0080] As the negative electrode active material 310, a material having the property of absorbing and releasing metal ions such as lithium ions can be used.

[0081] The negative electrode active material 310 may be at least one selected from the group consisting of carbon materials, metal materials, oxides, nitrides, tin compounds, silicon, silicon compounds, and titanium compounds. The metal material may be a single metal or an alloy. Examples of the metal material include lithium metal, lithium alloys, tin, and tin alloys. Examples of the carbon material include graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, and amorphous carbon.

[0082] The negative electrode active material 310 may contain at least one selected from the group consisting of a carbon material and an alloy-based active material that forms an alloy with lithium. Since the expansion rate of the carbon material during charging is relatively small, the use of the carbon material as the negative electrode active material 310 can improve the safety of the battery. The carbon material typically contains graphite. Graphite has a small expansion rate during the lithium ion insertion reaction, so it is suitable as the negative electrode active material 310. The theoretical capacity of the alloy-based active material is large. The use of the alloy-based active material can improve the energy density of the battery. Examples of the alloy-based active material include silicon, tin, silicon compounds, and tin compounds.

[0083] The negative electrode active material 310 has, for example, a particle shape. There is no particular limitation on the particle shape of the negative electrode active material 310. The particle shape of the negative electrode active material 310 may be spherical, elliptical, scaly, or fibrous.

[0084] Next, a method for producing the negative electrode material 3000 will be described.

[0085] First, a solution containing a coating material and a first solvent is prepared. The first solvent is a solvent capable of dissolving the coating material represented by formula (1). Examples of the first solvent include dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethanol, methanol, hexanal, N-methylpyrrolidone, acetophenone, tetrahydrofurfuryl alcohol, methyl benzoate, methyl salicylate, isophorone, ethyl cyanoacetate, diethyl malonate, 1,4-dichlorobutane, ethyl acetate, benzaldehyde, chloroacetone, pyridine, butyronitrile, and acrylonitrile. One selected from these solvents may be used alone as the first solvent, or a mixed solvent of two or more of them may be used as the first solvent.

[0086] Next, the solution is mixed with the negative electrode active material 310 to prepare a mixture. The first solvent is removed from the obtained mixture to coat the negative electrode active material 310 with the coating material. The first solvent may be removed from the mixture by leaving the mixture in the air at room temperature, or the first solvent may be volatilized from the mixture by heating the mixture. In this way, a powder of the coated active material 330 is obtained. According to such a method, the negative electrode active material 310 can be efficiently coated with the coating material. In consideration of removing the first solvent by heating, it is recommended to use a first solvent having a boiling point lower than the decomposition temperature of the coating material.

[0087] Furthermore, the solid electrolyte 300 and the negative electrode active material 310 coated with the coating material are kneaded using a second solvent in which the coating material is insoluble to prepare a slurry negative electrode material 3000. The slurry negative electrode material 3000 is applied to a negative electrode current collector to form a coating film, and the coating film is dried to obtain a negative electrode of a battery. The coating film may be dried by heating at a temperature higher than room temperature, or may be dried by leaving it in the air at room temperature. In the former method, a drying temperature of less than 300° C. is sufficient. According to the method of this embodiment, the negative electrode can be efficiently prepared by a wet method such as a coating method. The method of this embodiment is simple because it does not require drying at a high temperature.

[0088] The second solvent has a δp value lower than the δp value of the first solvent. The coating material and the solid electrolyte are insoluble in the second solvent. By using the second solvent, it is possible to prepare a negative electrode including the coated active material 330 and the solid electrolyte 300 while maintaining the coating layer 320. The "δp value" is the polarization term in the Hansen solubility parameter.

[0089] (Embodiment 2) Hereinafter, the second embodiment will be described. Descriptions that overlap with the first embodiment will be omitted as appropriate.

[0090] FIG. 2 is a cross-sectional view showing a schematic configuration of a battery 2000 in the second embodiment.

[0091] The battery 2000 in the second embodiment includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 .

[0092] The negative electrode 203 includes the negative electrode material 3000 in the embodiment 1. The advantages described in the embodiment 1 are obtained in the negative electrode 203.

[0093] The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .

[0094] According to the above configuration, the charge / discharge efficiency of the battery 2000 can be improved.

[0095] When the volume ratio of the negative electrode active material 310 to the solid electrolyte 300 (first solid electrolyte) in the negative electrode 203 is expressed as "v2:100-v2", the volume ratio v2 of the negative electrode active material 310 may satisfy 30≦v2≦95. When 30≦v2 is satisfied, the energy density of the battery 2000 is sufficiently ensured. Furthermore, when v2≦95 is satisfied, high-output operation is possible.

[0096] The thickness of the negative electrode 203 may be 10 μm or more and 500 μm or less. When the thickness of the negative electrode 203 is 10 μm or more, the energy density of the battery 2000 is sufficiently ensured. When the thickness of the negative electrode 203 is 500 μm or less, high-output operation is possible.

[0097] The positive electrode 201 includes a positive electrode active material and a solid electrolyte (third solid electrolyte). As the positive electrode active material, a material having a property of absorbing and releasing metal ions such as lithium ions can be used. As the positive electrode active material, a lithium-containing transition metal oxide, a transition metal fluoride, a polyanion material, a fluorinated polyanion material, a transition metal sulfide, a transition metal oxysulfide, a transition metal oxynitride, or the like can be used. In particular, when a lithium-containing transition metal oxide is used as the positive electrode active material, the manufacturing cost can be reduced and the average discharge voltage can be increased.

[0098] The positive electrode active material may contain Li and at least one element selected from the group consisting of Mn, Co, Ni, and Al. Such a material may be Li(NiCoAl)O 2 , Li(NiCoMn)O 2 , LiCoO 2 etc.

[0099] The positive electrode active material has, for example, a particle shape. The particle shape of the positive electrode active material is not particularly limited. The particle shape of the positive electrode active material may be needle-like, spherical, oval-spherical, or scaly.

[0100] The median diameter of the particles of the positive electrode active material may be 0.1 μm or more and 100 μm or less. When the median diameter of the particles of the positive electrode active material is 0.1 μm or more, the positive electrode active material and the solid electrolyte can form a good dispersion state in the positive electrode 201. As a result, the charge / discharge characteristics of the battery 2000 are improved. When the median diameter of the particles of the positive electrode active material is 100 μm or less, lithium diffusion within the particles of the positive electrode active material becomes fast. Therefore, the battery 2000 can operate at a high output.

[0101] The solid electrolyte of the positive electrode 201 may be at least one selected from the group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte. The oxide solid electrolyte has excellent high potential stability. By using the oxide solid electrolyte, the charge / discharge efficiency of the battery 2000 can be further improved.

[0102] When the volume ratio of the positive electrode active material to the solid electrolyte in the positive electrode 201 is expressed as "v1:100-v1", the volume ratio v1 of the positive electrode active material may satisfy 30≦v1≦95. When 30≦v1 is satisfied, the energy density of the battery 2000 is sufficiently ensured. Furthermore, when v1≦95 is satisfied, high-output operation is possible.

[0103] The thickness of the positive electrode 201 may be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 201 is 10 μm or more, the energy density of the battery 2000 is sufficiently ensured. When the thickness of the positive electrode 201 is 500 μm or less, high-output operation is possible.

[0104] When the solid electrolyte contained in the positive electrode 201 is particulate (e.g., spherical), the median diameter of the solid electrolyte particles may be 100 μm or less. When the median diameter is 100 μm or less, the positive electrode active material and the solid electrolyte can be well dispersed in the positive electrode 201. This improves the charge / discharge characteristics of the battery 2000.

[0105] The electrolyte layer 202 is a layer that includes an electrolyte. The electrolyte is, for example, a solid electrolyte. That is, the electrolyte layer 202 may be a solid electrolyte layer. Hereinafter, the solid electrolyte included in the electrolyte layer 202 is also referred to as a "second solid electrolyte."

[0106] The second solid electrolyte may be any of the materials exemplified in the embodiment 1. In other words, the electrolyte layer 202 may contain a solid electrolyte having the same composition as the solid electrolyte 300 contained in the negative electrode material 3000.

[0107] According to the above configuration, the charge / discharge efficiency of the battery 2000 can be further improved.

[0108] Alternatively, the electrolyte layer 202 may include a halide solid electrolyte having a composition different from the composition of the solid electrolyte 300 included in the anode material 3000 .

[0109] According to the above configuration, the output density and charge / discharge efficiency of the battery 2000 can be improved.

[0110] The halide solid electrolyte contained in the electrolyte layer 202 may contain Y as a metal element.

[0111] According to the above configuration, the output density and charge / discharge efficiency of the battery 2000 can be further improved.

[0112] The electrolyte layer 202 may include a sulfide solid electrolyte. Examples of the sulfide solid electrolyte include the solid electrolyte described in the first embodiment.

[0113] According to the above configuration, since the battery contains a sulfide solid electrolyte having excellent reduction stability, a low potential negative electrode material such as graphite or metallic lithium can be used, and the energy density of the battery 2000 can be improved.

[0114] The electrolyte layer 202 may include at least one selected from the group consisting of an oxide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte.

[0115] The oxide solid electrolyte is, for example, LiTi 2 (PO 4 ) 3 and its element-substituted NASICON-type solid electrolyte, (LaLi)TiO 3 Perovskite-type solid electrolyte based on Li 14 ZnGe 4 O 16 , Li 4 SiO 4 , LiGeO 4 and its element-substituted LISICON-type solid electrolytes, Li 7 La 3 Zr 2 O 12 and its element-substituted garnet-type solid electrolytes, Li 3 N and its H-substituted derivatives, Li 3 PO 4 and its N-substituted derivative, LiBO 2 , Li 3 BO 3 Li-BO compounds such as 2 SO 4 , Li 2 CO 3 Glass or glass ceramics to which such materials are added can be used.

[0116] As the polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used. The polymer compound may have an ethylene oxide structure. By having an ethylene oxide structure, the polymer compound can contain a large amount of lithium salt, so that the ionic conductivity can be further increased. As the lithium salt, LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiSO 3 CF 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ), LiC(SO 2 CF 3 ) 3 As the lithium salt, one type of lithium salt selected from these may be used alone, or a mixture of two or more types of lithium salts selected from these may be used.

[0117] The complex hydride solid electrolyte is, for example, LiBH 4 - LiI, LiBH 4 -P 2 S 5 etc. can be used.

[0118] The electrolyte layer 202 may contain the second solid electrolyte as a main component. That is, the electrolyte layer 202 may contain the second solid electrolyte in a mass ratio of 50% or more (i.e., 50 mass% or more) to the total mass of the electrolyte layer 202.

[0119] According to the above configuration, the charge / discharge characteristics of the battery 2000 can be further improved.

[0120] The electrolyte layer 202 may contain the second solid electrolyte in a mass ratio relative to the total mass of the electrolyte layer 202 of 70% or more (ie, 70 mass % or more).

[0121] According to the above configuration, the charge / discharge characteristics of the battery 2000 can be further improved.

[0122] The electrolyte layer 202 contains the second solid electrolyte as a main component, and may further contain unavoidable impurities, or starting materials, by-products, decomposition products, and the like used in synthesizing the second solid electrolyte.

[0123] The electrolyte layer 202 may contain 100% of the second solid electrolyte in terms of mass percentage relative to the total mass of the electrolyte layer 202 (ie, 100 mass %), excluding unavoidable impurities.

[0124] According to the above configuration, the charge / discharge characteristics of the battery 2000 can be further improved.

[0125] As described above, the electrolyte layer 202 may be composed of only the second solid electrolyte.

[0126] The electrolyte layer 202 may contain only one type of solid electrolyte selected from the above-mentioned group of solid electrolytes, or may contain two or more types of solid electrolytes selected from the above-mentioned group of solid electrolytes. The multiple solid electrolytes have different compositions. For example, the electrolyte layer 202 may contain a halide solid electrolyte and a sulfide solid electrolyte.

[0127] The thickness of the electrolyte layer 202 may be 1 μm or more and 300 μm or less. When the thickness of the electrolyte layer 202 is 1 μm or more, the positive electrode 201 and the negative electrode 203 can be more reliably separated. When the thickness of the electrolyte layer 202 is 300 μm or less, high-output operation can be achieved.

[0128] At least one of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder in order to improve the adhesion between particles. The binder is used to improve the binding property of the material constituting the electrode. Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, and carboxymethyl cellulose. The binder may be a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. Two or more of these materials may be mixed and used as the binder.

[0129] At least one of the positive electrode 201 and the negative electrode 203 may contain a conductive assistant for the purpose of increasing electronic conductivity. Examples of the conductive assistant include graphites such as natural graphite or artificial graphite, carbon blacks such as acetylene black and ketjen black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymer compounds such as polyaniline, polypyrrole, and polythiophene. When a carbon conductive assistant is used, costs can be reduced.

[0130] The positive electrode 201 and the negative electrode 203 may each have a current collector. Examples of materials for the current collector include aluminum, aluminum alloys, stainless steel, copper, and nickel.

[0131] The battery 2000 in the second embodiment can be configured as batteries of various shapes, such as a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, and a laminated type. EXAMPLES

[0132] Hereinafter, the present disclosure will be described in detail using examples and comparative examples.

[0133] [Preparation of sulfide solid electrolyte] Li was dissolved in water in a glove box with an Ar atmosphere at a dew point of -60°C or less. 2 S and P 2 S 5 and Li in molar ratio 2 S:P 2 S 5 The mixture was weighed so that the ratio of the sulfide and the glassy solid electrolyte was 75:25. These were ground and mixed in a mortar to obtain a mixture. The mixture was then milled at 510 rpm for 10 hours using a planetary ball mill (Fritsch, P-7 type) to obtain a glassy solid electrolyte. The glassy solid electrolyte was heat-treated in an inert atmosphere at 270°C for 2 hours. As a result, a glass-ceramic sulfide solid electrolyte, Li 2 SP 2 S 5 A powder of 100 g was obtained.

[0134] <<Example 1>> [Preparation of coated active material] In a glove box with an Ar atmosphere at a dew point of -60°C or less, 0.12 g of LiSO 3 F was dissolved in 9.88 g of dimethyl carbonate to obtain a lithium sulfonate solution with a concentration of 1.2 mass %.

[0135] 10g LiSO 3The F solution was mixed with 10 g of graphite, left at room temperature for 24 hours, and then dried at 105 °C for 8 hours. As a result, LiSO 3 F-coated graphite was obtained.

[0136] [Preparation of negative electrode material] The coated active material and the sulfide solid electrolyte were mixed in a mass ratio of 7:3 in a glove box in an Ar atmosphere with a dew point of −60° C. or less. Thus, a negative electrode material of Example 1 was obtained.

[0137] [Battery construction] The following steps were carried out using the negative electrode material, sulfide solid electrolyte, and copper foil (thickness 12 μm).

[0138] First, 10 mg of the sulfide solid electrolyte and 10 mg of the negative electrode material were laminated in an insulating outer cylinder, and then pressed at a pressure of 360 MPa to obtain a laminate of the negative electrode active material layer and the electrolyte layer.

[0139] Next, a copper foil was laminated on the negative electrode active material layer, and the resultant was pressure molded at 360 MPa to obtain a laminate of the negative electrode current collector, the negative electrode active material layer, and the electrolyte layer.

[0140] Next, metal In (thickness 200 μm), metal Li (thickness 300 μm), and metal In (thickness 200 μm) were laminated on the electrolyte layer in this order, and these were press-molded at a pressure of 80 MPa to produce a laminate consisting of a positive electrode, an electrolyte layer, and a negative electrode.

[0141] Next, stainless steel current collectors were placed on the top and bottom of the laminate, and current collecting leads were attached to the current collectors.

[0142] Finally, the insulating outer cylinder was sealed using an insulating ferrule to isolate the inside of the insulating outer cylinder from the outside atmosphere, thereby producing the battery of Example 1.

[0143] <<Example 2>> [Preparation of coated active material] 10g LiSO 3The F solution was mixed with 9 g of graphite and 1 g of silicon, and the mixture was left at room temperature for 24 hours, and then dried at 105 °C for 8 hours. As a result, LiSO 3 F-coated graphite and LiSO 3 A mixed active material was obtained with silicon coated with F. Graphite and Si were used in powder form.

[0144] [Preparation of negative electrode material] The mixed active material and the sulfide solid electrolyte were mixed in a mass ratio of 7:3 in a glove box in an Ar atmosphere with a dew point of −60° C. or less. Thus, a negative electrode material of Example 2 was obtained.

[0145] [Battery construction] A battery of Example 2 was produced in the same manner as in Example 1, except that 5 mg of the negative electrode material of Example 2 was used instead of the negative electrode material of Example 1.

[0146] <<Example 3>> [Preparation of coated active material] In a glove box with an Ar atmosphere at a dew point of -60°C or less, 0.6 g of LiPO 2 F 2 was dissolved in 9.94 g of dimethyl carbonate. This resulted in a LiPO 2 F 2 A solution was obtained.

[0147] [Preparation of negative electrode material] 10g LiPO 2 F 2 The solution was mixed with 10 g of graphite, and the mixture was left at room temperature for 24 hours, and then dried at 105°C for 8 hours. As a result, LiPO 2 F 2 Thus, graphite coated with

[0148] [Battery construction] A battery of Example 3 was produced in the same manner as in Example 1, except that the negative electrode material of Example 3 was used instead of the negative electrode material of Example 1.

[0149] <<Comparative Example 1>> A battery of Comparative Example 1 was produced in the same manner as in Example 1, except that graphite without a coating layer was used as the negative electrode active material.

[0150] <<Comparative Example 2>> A battery of Comparative Example 2 was produced in the same manner as in Example 2, except that a mixture of graphite without a coating layer and silicon without a coating layer was used as the negative electrode active material.

[0151] <<Comparative Example 3>> A battery of Comparative Example 3 was fabricated in the same manner as in Example 1, except that 7.7 mg of graphite without a coating layer was used as the negative electrode active material.

[0152] <<Comparative Example 4>> [Preparation of coated active material] In a glove box in an Ar atmosphere with a dew point of −60° C. or less, graphite was coated with amorphous carbon according to the method disclosed in Patent Document 1 to obtain a coated active material.

[0153] [Preparation of negative electrode material] The coated active material and the sulfide solid electrolyte were mixed in a mass ratio of 7:3 in a glove box in an Ar atmosphere with a dew point of −60° C. or less. Thus, a negative electrode material of Comparative Example 4 was obtained.

[0154] [Battery construction] A battery of Comparative Example 4 was produced in the same manner as in Example 1, except that 10 mg of the negative electrode material of Comparative Example 4 was used instead of the negative electrode material of Example 1.

[0155] <<Comparative Example 5>> As the coating material, LiFSI(LiN(SO 2 F) 2 A battery of Comparative Example 5 was produced in the same manner as in Example 1, except that ) was used.

[0156] <<Comparative Example 6>> [Preparation of coated active material] In a glove box with an Ar atmosphere at a dew point of -60°C or less, 0.6 g of LiPF 6 was dissolved in 9.94 g of dimethyl carbonate. This resulted in a LiPF with a concentration of 0.6 mass%. 6 A solution was obtained.

[0157] [Preparation of negative electrode material] 10g LiPF 6 The solution was mixed with 10 g of graphite, and the mixture was left at room temperature for 24 hours, and then dried at 105°C for 8 hours. As a result, LiPF 6 Thus, graphite coated with

[0158] [Battery construction] A battery of Comparative Example 6 was produced in the same manner as in Example 1, except that the negative electrode material of Comparative Example 6 was used instead of the negative electrode material of Example 1.

[0159] [Charge / discharge test] Using the batteries of Examples 1 to 3 and Comparative Examples 1 to 6, charge / discharge tests were carried out under the following conditions.

[0160] The battery was placed in a thermostatic chamber at 25°C.

[0161] The battery was charged at a constant current of 380 μA, which corresponds to a 0.05 C rate (20 hour rate) relative to the theoretical capacity of the battery, and charging was terminated at a voltage of −0.62 V.

[0162] Next, the battery was discharged at a constant current of 380 μA, which corresponds to a 0.05 C rate (20 hour rate), and the discharge was terminated at a voltage of 1.9 V. However, in the battery of Comparative Example 3, the current value was 292 μA.

[0163] Furthermore, the battery was charged at a constant current of 380 μA, which corresponds to a 0.05 C rate (20 hour rate) relative to the theoretical capacity of the battery, and charging was terminated at a voltage of −0.62 V. However, in the battery of Comparative Example 3, the current value was 292 μA. The charging capacity at this time was recorded as the “0.05 C charging capacity”.

[0164] Furthermore, the batteries of the examples and comparative examples were discharged at a constant current of 0.05C rate (20 hour rate), and then charged at a constant current of 10 times the current, 3800μA, and charging was terminated at a voltage of -0.62V. However, in the battery of comparative example 3, the current value was 2920μA. The charging capacity at this time was recorded as "0.5C charging capacity".

[0165] The ratio of the 0.05C charge capacity to the 0.05C charge capacity of the batteries of the Example and Comparative Example was calculated. In addition, the ratio of the 0.05C charge capacity of each battery to the 0.05C charge capacity of the battery of Example 1 was also calculated. The results are shown in Table 1.

[0166] [Table 1]

[0167] <<Considerations>> The ratio of (0.5C charging capacity) / (0.05C charging capacity) reflects the charging rate characteristics. In other words, the higher the value of (0.5C charging capacity) / (0.05C charging capacity), the shorter the charging time.

[0168] As shown in Table 1, the (0.5C charge capacity) / (0.05C charge capacity) value of the battery of Example 1 was higher than that of Comparative Example 1. 3 By coating F, the charge rate characteristics were improved.

[0169] Generally, coating the surface of an active material with an inorganic compound that does not have lithium ion conductivity creates a barrier to the movement of lithium ions and creates resistance, so it is rare to select such an inorganic compound as a coating material for improving the charge rate characteristics.

[0170] However, surprisingly, in the battery of Example 1, LiSO 3The charge rate characteristics were improved by using F as the coating material. The reason for this is thought to be related to the concentration of lithium ions in the coating layer. According to the battery of the embodiment, since the concentration of lithium in the coating layer is high, lithium ions are smoothly taken into the negative electrode active material during charging, and as a result, the charge rate characteristics are thought to be improved.

[0171] As can be seen from the comparison between Example 2 and Comparative Example 2, the same effect was obtained even when an alloy-based active material was used as the negative electrode active material.

[0172] As can be seen from the results of Example 3, LiPO 2 F 2 A significant effect was also obtained when it was used as a coating material.

[0173] On the other hand, the Li source in Comparative Example 1 and Comparative Example 2 is limited to Li contained in the solid electrolyte. Therefore, it is considered that the charge rates of the batteries in Comparative Example 1 and Comparative Example 2 were inferior to the charge rate characteristics of the battery in the Example.

[0174] The charge rate characteristic of the battery of Comparative Example 3 was equivalent to that of the battery of Example 1. However, in Comparative Example 3, the amount of the negative electrode active material used was reduced, so that the charge capacity of the battery of Comparative Example 3 was significantly lower than that of the battery of Example 1. Comparative Example 3 shows that it is possible to improve the charge rate characteristic by sacrificing the energy density of the battery. However, Comparative Example 3 is not desirable from the viewpoint of the energy density of the battery.

[0175] The charge rate characteristic of the battery of Comparative Example 4 was significantly lower than those of the other batteries. The amorphous carbon coating layer not only did not have the effect of improving the charge rate characteristic of the solid-state battery, but also reduced the charge rate characteristic.

[0176] In the battery of Comparative Example 5, the graphite was coated with a lithium salt (LiFSI) containing nitrogen (N) in the anion. As can be understood by comparing the results of Comparative Example 1 and Comparative Example 5, coating the graphite with LiFSI did not improve the charge rate characteristics. This shows that the same effect cannot be obtained regardless of the type of lithium salt used.

[0177] In the battery of Comparative Example 6, LiPF 6 As can be seen from a comparison of the results of Example 1, Comparative Example 1, and Comparative Example 6, the graphite was coated with LiPF 6 Although the coating layer improved the charge rate characteristics, the effect was limited. [Industrial Applicability]

[0178] The battery of the present disclosure can be used, for example, as an all-solid-state lithium secondary battery.

Claims

1. A negative electrode active material; A solid electrolyte; A coating material that coats the negative electrode active material; Including, The coating material is represented by the following composition formula (1): Li a A b X c ・・・(1) where a, b, and c are positive real numbers, A is S, X is F and O; The coating material comprises SO x F y groups; Negative electrode material.

2. The coating material is LiSO 3 Including F. The negative electrode material according to claim 1 .

3. The coating material further comprises a material containing a PO x F y group. The negative electrode material according to claim 1 or 2.

4. The coating material further comprises a material containing Li, P, O and F. The negative electrode material according to claim 1 or 2.

5. The coating material further comprises LiPO2F2. The negative electrode material according to claim 1 or 2.

6. The thickness of the layer of the coating material is 0.5 nm or more and 20 nm or less; The negative electrode material according to any one of claims 1 to 5.

7. The solid electrolyte includes at least one selected from the group consisting of a sulfide solid electrolyte, a halide solid electrolyte, and an oxyhalide solid electrolyte. The negative electrode material according to any one of claims 1 to 6.

8. The negative electrode active material includes at least one selected from the group consisting of a carbon material and an alloy-based active material that forms an alloy with lithium. The negative electrode material according to any one of claims 1 to 7.

9. The negative electrode active material includes graphite. The negative electrode material according to any one of claims 1 to 8.

10. The solid electrolyte has lithium ion conductivity. The negative electrode material according to any one of claims 1 to 9.

11. A negative electrode comprising the negative electrode material according to any one of claims 1 to 10; A positive electrode and an electrolyte layer provided between the positive electrode and the negative electrode; Equipped with a battery.

12. A method for producing a negative electrode material including a negative electrode active material and a coating material that coats the negative electrode active material, preparing a solution containing the coating material and a first solvent; mixing the solution with the negative electrode active material to prepare a mixture; removing the first solvent from the mixture to coat the negative electrode active material with the coating material; a second solvent in which the coating material is insoluble is used to knead a solid electrolyte and the negative electrode active material coated with the coating material to prepare a slurry of the negative electrode material; A method for producing anode materials.

Citation Information

Patent Citations

  • Negative electrode mixture, electrode, and lithium ion battery

    JP2015002054A

  • Lithium secondary battery anode and lithium secondary battery

    JP4729716B2

  • Graphite material for lithium ion secondary batteries, method for producing same, negative electrode and lithium ion secondary battery

    WO2018083937A1

  • Reduced graphene-based material

    WO2019235469A1